Functional microbiomics: Evaluation of gut microbiota-bile acid metabolism interactions in health and disease. - Mullish,BH; Pechlivanis,A; Barker,GF; Thursz,MR; Marchesi,JR; McDonald,JAK (Methods (San Diego, Calif.), 2018)
There is an ever-increasing recognition that bile acids are not purely simple surfactant molecules that aid in lipid digestion, but are a family of molecules contributing to a diverse range of key systemic functions in the host. It is now also understood that the specific composition of the bile acid milieu within the host is related to the expression and activity of bacterially-derived enzymes within the gastrointestinal tract, as such creating a direct link between the physiology of the host and the gut microbiota. Coupled to the knowledge that perturbation of the structure and/or function of the gut microbiota may contribute to the pathogenesis of a range of diseases, there is a high level of interest in the potential for manipulation of the gut microbiota-host bile acid axis as a novel approach to therapeutics. Much of the growing understanding of the biology of this area reflects the recent development and refinement of a range of novel techniques; this study applies a number of those techniques to the analysis of human samples, aiming to illustrate their strengths, drawbacks and biological significance at all stages. Specifically, we used microbial profiling (using 16S rRNA gene sequencing), bile acid profiling (using liquid chromatography-mass spectrometry), bsh and baiCD qPCR, and a BSH enzyme activity assay to demonstrate differences in the gut microbiota and bile metabolism in stool samples from healthy and antibiotic-exposed individuals.